Effect of bedtime social media use on quality of sleep among adolescents in selected schools and pre-university colleges, Bangalore - Thounaojam, Monika; S., Radha M.; N., Vanitha (International Journal of Research in Medical Sciences, 2024)
Background: Social media has grown extensively among the adolescent population. However, excessive use at bedtime is reported to affect their quality of sleep. Sleep is very important for the normal growth and development of a child; meanwhile, inadequate sleep poses numerous health risks. The study was conducted with the objective to assess the impact of bedtime social media usage on the quality of sleep among adolescents and to find the relationship with socio-demographic variables. Methods: A descriptive survey was conducted for the study. Non-probability purposive sampling technique along with inclusion and exclusion criteria was used to select 150 adolescents. Socio-demographic data and Pittsburgh sleep quality index (PSQI) were administered to assess bedtime social media use and quality of sleep. Results: There was a weak positive correlation (r=0.262) between bedtime social media use and quality of sleep which is statistically significant (p=0.001). A statistically significant association was found between quality of sleep and standard (p=0.003), usual bedtime for the past month (p=0.000), hours slept during weekdays (p=0.000), and hours of social media use at bedtime (p=0.000). Conclusions: Regardless of the health risk posed by inadequate sleep due to overindulgence of social media at bedtime, its exploitation among adolescents is still on the rise. Therefore, the findings suggest that it is very crucial to give awareness and education regarding healthy use of social media and good quality of sleep in order to live a healthy and productive life in the future.